Analisis Pengaruh Economic Value Added, Market Value Added, dan Return Saham Terhadap Price to Book Value - Kumairoh, Rini; Widiastuti, C. Tri; Setiawati, Ira (JAB (Jurnal Akuntansi & Bisnis), 2025)
This research seeks to assess the influence of Economic Value Added, Market Value Added, and Stock Returns on the Price to Book Value of energy sector firms listed on the Indonesia Stock Exchange from 2021 to 2023.  The used technique is a quantitative approach using a causal-comparative research design.  This study employs secondary data obtained from the financial statements of energy sector firms, available on the official websites of IDX and Indopremier.com. “The population of this research comprises all energy sector businesses listed on the IDX, whereas the sample consists of 38 companies chosen using a purposive selection procedure based on particular criteria.  This research identifies Economic Value Added (X1), Market Value Added (X2), and stock returns (X3) as independent variables, with Price to Book Value (Y) serving as the dependent variable.  Panel data regression, classical assumption evaluations, t-tests, and coefficient of determination analyses are used for data analysis.  Data processing is conducted with EViews 12 software.  The study's findings reveal that Economic Value Added does not significantly influence Price to Book Value, whereas Market Value Added and stock returns do have a considerable impact on Price to Book Value.  Keywords: EVA, MVA, Stock Return, Energi Sector